Comparison in Wrist Splints and Wrist-Metacarpophalangeal Splints Use for Patients with Carpal Tunnel Syndrome Evi - Evi Yuliani; Vitriana; Widjajalaksmi Kusumaningsih; Hadyana Sukandar (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : To compare the effect of both wrist splint and wrist-metacarpophalangeal splint at night using Symptom Severity Scale (SSS) and Functional Status Scale (FSS) and to know the validity andreliability of Indonesian version of SSS dan FSS.Methods : This study enrolled 19 subjects in each of the two groups that were given neutral wrist splint and exercise in one group (group A) and neutral wrist-metacarpophalangeal splint and exercise in theother group (group B).Results : Indonesian version of SSS and FSS have been proven valid with rs lowest = 0.360 and highest 0.810(>0.3) and relable with α SSS=0.762 dan FSS=0.781 (>0.7). There were significant improvement score of SSS and FSS in each group with p value <0.001. There were greater functional improvement in group treated with wrist-metacarpophalangeal splint (group B) with p value = 0.036 (p<0.05) Conclusions: There was improvement of SSS and FSS in both groups of study with greater improvement of in wrist-hand splint group.Keywords: Carpal Tunnel Syndrome, wrist splint, wrist-hand splint,,nerve and tendon gliding, SSS, FSS.